Cultivating the Organizational Cultural Values of Jambi Province Human Resources Development Agency - Lailatul Isnaini (Badan Pengembangan Sumber Daya Manusia (BPSDM) Provinsi Jambi, 2020)
This research is a type of qualitative research on organizational culture (organization culture) that was developed in the Human Resources Development Agency (BPSDM) Jambi Province. Organizational culture (organization culture) is an important concept in the organization. An in-depth understanding of this concept is important given the interrelationship between the concept and the application of the two things. Incorrect understanding of the concept can make it difficult for regulators/regulators, practitioners, and management in communicating about organizational culture. Based on this study, the writer finally tries to come up with a general picture of the application of organizational culture in the Jambi Province Human Resources Development Agency. The results of the study show that organizational culture has been believed to be basic values, norms, and beliefs, and is spread among all members of the organization through social interaction both among members or members of the organization, which is reflected in the behavior of individuals and their organizations. So that in carrying out the task of promoting professionalism, responsibility, integrity, cooperation, and being disciplined in accordance with applicable rules.